Differences in Muscle Activities and Kinematics between Forefoot Strike and Rearfoot Strike in the Lower Limb during 180° Turns - Naruto Yoshida; Shun Kunugi; Takehiro Konno; Akihiko Masunari; Satoru Nishida; Takashi Koumura; Naoyuki Kobayashi; Shumpei Miyakawa (International Journal of Sports Physical Therapy)
# Background